혼합트래픽 환경에서 Open Flow 네트워크 성능 평가 - 염재근(Jae Keun Yeom); 이창무(Chang-Moo Lee); 최덕재(Deok Jae Choi); 석승준(Seung Jun Seok); 송왕철(Wang Cheol Song); 허지완(Jee-Wan Huh) (한국콘텐츠학회 논문지, 12(12), 2012)
The traffic in research network for the new structure of the network and new service research has the various properties. From the perspective of a specific traffic point of view, transmission of traffic with different requirements using a single routing protocol is an obstacle to satisfy requirements. In this study, we classify the properties of the traffic into two types. We propose the way that we can get the overall optimization effect, the experiment proves it by providing independent multiple forwarding path by applying optimized algorithm by types. In order to distinguish each type of traffic we use the ports on the switch and in order to implement independent path we apply OpenFlow system. In other words, we present the measure that can be implemented to improve the satisfaction of the traffic by making multiple paths by OpenFlow controller according to the type of traffic and by enforcing in Forwarder. 네트워크의 새로운 구조와 신개념 서비스 연구를 위한 연구망에서의 트래픽은 매우 다양한 속성을 지니게 된다. 이러한 연구망에서 단일 라우팅 프로토콜을 이용하는 것은 다양한 트래픽 속성을 만족시키는데 한계가 있다. 본 연구에서는 트래픽 특성을 두 가지 유형으로 분류하고 각 유형별로 최적화 기법을 이용한 알고리즘을 적용하여 독립적인 다중 포워딩 경로를 제공함으로써, 전체적으로 최적화 효과를 얻을 수 있는 방안을 제시하고, 실험으로 이를 입증한다. 구분된 유형별 트래픽은 스위치의 각 포트별로 할당되며, 각 유형별 포워딩 경로를 제공하기 위하여 OpenFlow 기술을 사용한다. 즉, 하나의 망에 트래픽 유형별로 복수 개의 경로를 OpenFlow Controller에서 구동하여 그 결과를 Forwarder에서 실행함으로써 트래픽의 만족도를 향상 시키는 시스템을 구현할 수 있는 방안을 제시한다.